2011
DOI: 10.1016/j.jjcc.2011.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial thrombus and prognosis after anticoagulation therapy in patients with atrial fibrillation

Abstract: We demonstrated that LAT was a univariate risk factor associated with worse cardiovascular outcomes, which was observed in 8.8% of patients with sub-therapeutic anticoagulation and 3.6% of patients with sufficient anticoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 34 publications
4
43
0
1
Order By: Relevance
“…5 The PT-INR value in our study was also relatively low (1.9 ± 0.6), which may have contributed to the higher frequency of LAAT. 24 PT-INR and TTR are generally considered the better markers for adequate warfarinization, as patients with PT-INR of 2.0-3.0 or TTR >60-65% were reported to be at lower risk of stroke. 18 19 However, in the present study, there are no significant differences in PT-INR and TTR between the M A N U S C R I P T…”
Section: Discussionmentioning
confidence: 99%
“…5 The PT-INR value in our study was also relatively low (1.9 ± 0.6), which may have contributed to the higher frequency of LAAT. 24 PT-INR and TTR are generally considered the better markers for adequate warfarinization, as patients with PT-INR of 2.0-3.0 or TTR >60-65% were reported to be at lower risk of stroke. 18 19 However, in the present study, there are no significant differences in PT-INR and TTR between the M A N U S C R I P T…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this study was conducted in non valvular atrial fibrillation population which did not reflect our patient situation closely. 8 Jaber et al 9 found thrombus resolution in 80.1% of patients who received anticoagulation for 47±18 days. Contrast to plenty of data available on the usage of warfarin, the data of lumbrokinase for left atrial thrombus are limited.…”
Section: Discussionmentioning
confidence: 97%
“…20 Cheol et al 21 found six of nine patients with adequate anticoagulation with warfarin had persistent trombi eventhough the size of thrombi decreased from 2.2±0.8 cm to 0.9±1.0 cm. 21 A study conducted by Fukuda et al 8 revealed a better result, left atrial thrombus was found in 8.8% of patients with sub-therapeutic anticoagulation therapy and in 3.6% of patients with sufficient anticoagulation therapy. Nevertheless, this study was conducted in non valvular atrial fibrillation population which did not reflect our patient situation closely.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In two other studies with small patient numbers, resolution rates of [80 % were reported after 4 weeks of treatment with warfarin with a target INR C21 [7,18]. However, due to differences in patient populations, anticoagulant treatment duration, effective INR levels, and thrombus visualization by TEE, it is difficult to compare these studies [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%